Tradisi “Ngidu Urasan” Studi Living Qur`an Di Desa Surulangun - dan Moh. Jufriyadi Sholeh, Rita Desrianti (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2020)
The Ngidu Urasan tradition is an interaction carried out by the community in Surulangun Village, Rawas Ulu District, Muratara Regency who carries out the tradition of Ngidu Urasan as a practice to help people who are sick with the intermediary of Rambutan leaves which are read the verses of the Qur'an. Whereas previously there were many patterns of interaction with the Koran that were carried out by the Muslim community such as reading, memorizing, amulet, syifa` and so on. So to find out more about this tradition, in this article the researcher will use the Living Qur`an Study to dissect the theme so that the al-Qur'an text really lives in the Surulangun village community by using a qualitative approach and descriptive type of research. qualitative non-participants, namely by means of documentation and in-depth interviews with informants about the practice of the ngidu urasan tradition to collect data from the research location in order to describe and analyze a research result. And the focus of this research is centered on the people of Surulangun village who believe that the tradition of ngidu urasan is a medium of healing for diseases such as fever, high fever and spirits disorders (Tesapo).This research concludes that the tradition of ngidu urasan originates from previous ancestors and is based on the beliefs and beliefs of the people in the figures (pengidu) who practice ngidu urasan. Pengidu urasan has its own practice by using rambutan leaves that are recited from the holy verses of al-Qur`an such as al-Fatihah, An-Nass, al-Ikhlas, al-Falaq, Qursi verses, Sholawat Nabi, al-Zalzalah as a treatment medium for fever. , high heat and disturbance of spirits. So that angidu urasan becomes a study in the study of living qur`an, namely the al-Qur`an that lives in a society and functions as a healing medicine.